Gestão da comunicação em organizações públicas: um estudo de caso da Assembleia Legislativa de Mato Grosso do Sul - Evellyn Delgado Abelha (2023)
Both national and international literature reavel the importance of communication management to all forms of organizations. Among the practices to apply communication management is the formalization of processes, which is made through administration, planning, communication policies and definition of the target audience tools. Studies show that the communication sectors andthe professionals in this área do not use these resources quite enough, in spite of being strategic elements. This happens not only in private institutions but also in public ones. This reality was observed in Assembleia Legislativa do Estado de Mato Grosso do Sul (Alems) Communication Department. Taking this into account, the general purpose of this study was to suggest a communication management guide applied to the contexto of this institution, as it does not have any communication policies, planning or processes formally established and shared. In order to build up this guide, a bibliography study on management and communication in institutions was held. Based on thes selected studies, basic tools on communication management were listed. Afterwards, interviews with communication managers at Assembleia Legislativa identified how this management is accomplished in the entity. A thorough analysis of the gathered material showed Alems’ needs to adopt management tools to raise communication actions from an operational level to a more strategic degree. The non-use of management tools evidenced some weaknesses in the strategic conduction of communication at Alems, among which are: lack of alignment in the discourses of managers; processes and actions that are more subject to momentary decisions and with a strong tendency to be interpreted and based on the experience of managers; isolated and fragmented initiatives of communication management; absence of major guidelines which would guide the communication department as a whole. Therefore, a document containing basic tools was build so that the public institituion could administrate its communication acts in a formal and strategic way. Besides contributing in practical manners to the improvement of public adminstration management tools, this study also helped to increase the number of researches on management tools in the communication sector, which has insuficiente studies, not only in Brazil but also abroad, regarding the importance of this subject.